2018
DOI: 10.1186/s40643-018-0222-8
|View full text |Cite
|
Sign up to set email alerts
|

Self-cloning CRISPR/Cpf1 facilitated genome editing in Saccharomyces cerevisiae

Abstract: Background: Saccharomyces cerevisiae is one of the most important industrial microorganisms. A robust genome editing tool is vital for both fundamental research and applications. To save the time and labor consumed in the procedure of genome editing, a self-cloning CRISPR/Cpf1 system (scCRISPR/Cpf1), in which a self-cleaving plasmid and PCR-generated site-specific crRNA fragment were included, was developed. Results: Using scCRISPR/Cpf1 as the genetic tool, simple and fast singleplex and multiplex genomic inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The differences in regard of expression of the chromosomally integrated mRFP and sfGFP genes will need further investigations but can be linked to differences in the necessary promoter and RBS sequences. Furthermore, as the conjugation efficiency obtained from multiplexing approaches was rather low, optimization of transformation procedure might improve the efficiency for multiplex integration. , Previous studies have reported CRISPR-Cas-based multiplex genetic engineering in different microorganisms. However, only a few demonstrated multiplex gene integration, which was mainly performed in yeast. , While it has been reported in E. coli, to the best of our knowledge, our study is the first to utilize a Cas9-based system to achieve multiplex gene integrations in Gram-positive bacteria.…”
Section: Resultsmentioning
confidence: 92%
“…The differences in regard of expression of the chromosomally integrated mRFP and sfGFP genes will need further investigations but can be linked to differences in the necessary promoter and RBS sequences. Furthermore, as the conjugation efficiency obtained from multiplexing approaches was rather low, optimization of transformation procedure might improve the efficiency for multiplex integration. , Previous studies have reported CRISPR-Cas-based multiplex genetic engineering in different microorganisms. However, only a few demonstrated multiplex gene integration, which was mainly performed in yeast. , While it has been reported in E. coli, to the best of our knowledge, our study is the first to utilize a Cas9-based system to achieve multiplex gene integrations in Gram-positive bacteria.…”
Section: Resultsmentioning
confidence: 92%
“…[24][25][26] However, only a few successfully demonstrated multiplex gene integrations, which was mainly performed in yeast. 27,28 While multiplex gene insertion has been reported in E. coli, 29 to the best of our knowledge, our study is the first to utilize a Cas9-based system to achieve multiplex gene integrations in Gram-positive bacteria.…”
Section: Resultsmentioning
confidence: 96%
“…One important Cas protein that has been employed for genome editing is the Cas12a enzyme (also known as Cpf1), which recognizes a T-rich PAM motif ( Nakade et al, 2017 ; Yan et al, 2019 ; Paul and Montoya, 2020 ; Thompson et al, 2021 ) ( Table 2 ). Genome editing using Cas12a has a number of differences from Cas9 for genome editing in yeast: first, it does not require tracrRNA, therefore their sgRNAs are shorter relative to Cas9; second, it can process multiple crRNAs from a single crRNA array, whereas for Cas9 one must express crRNAs separately or process gRNAs using additional enzymes; third, its PAM motif is located on the 5’ end of the target DNA sequence whereas this is on the 3’ end for Cas9; and finally Cas12a generates staggered or sticky DSBs containing overhangs, often leading to deletions and point mutations ( Świat et al, 2017 ; Zetsche et al, 2017 ; Li Z.-H. et al, 2018 ; Verwaal et al, 2018 ; Ciurkot et al, 2019 ; Ciurkot et al, 2021 ). These properties of Cas12a make multiplexing experiments relatively simple relative to those for Cas9 which require multiple or even complex expression constructs.…”
Section: Practical Considerations For Crispr Genome Editing In Yeastmentioning
confidence: 99%